Multipathways for the Synthesis of Fused Bicyclic 2-Aminothiazolyl Compounds Tuned by Ring Size - Liu, Pengfei; Shen, Hongfeng; Shao, Xusheng; Li, Zhong; Xu, Xiaoyong (Synlett, 2014)
A new methodology for the synthesis of fused bicyclic 2-aminothiazolyl compounds has been developed, using cyclocondensation of aromatic thioureas with α,β-epoxy cycloketones in alcohol under microwave irradiation without any catalyst. The product distribution is related to the ring size of α,β-epoxy cycloketones. Mechanistic studies suggest that the reactions share analogous bicyclic dihydroxy intermediates but undergo different further reactions to give diverse products.
Keywords: thiazole; fused bicyclic; ring size; multipathways; microwave irradiation